EXTENSION METHODS IN IMPROVEMENT OF AGRICULTURE ON RURAL FARMS IN VOJVODINA - Čikić, Jovana; Petrović, Živojin; Janković, Dejan (Economics of Agriculture, 2009)
Improvement of production on agricultural farms as an extension goal, in fact, implies change in attitudes, opinions as well as farmers behaviour. Such changes are achievable through the process of adoptation of new knowledge, technologies and know-hows which enable farmer to solve problems of agricultural production. Extension agent has a task to facilitate such process. As a basic mechanism of diffusion of needed knowledge and know-hows is use of extension methods. The paper focuses on work of extension agents in Agricultural Extension Service of Autonomus Province of Vojvodina. Data for the analysis are collected by Extension service Typology from July 2007. to December 2008. The aim of the paper is to indicate the importance of complementary use of extension methods.